24-hours variation of amount and contents of wastewater flowing to treatment plant in Zielona Góra = Zmienność dobowa ilości i składu ścieków dopływających do oczyszczalni w Zielonej Górze - Myszograj, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article describes daily variations of influents in the aspect of their volume and composition in the sewage treatment plant of Zielona Góra. With a method of direct measurements the flow rate and the concentration of pollutants in the sewage have been marked. Based on the research results the cumulative curves of the flow duration and daily pollutant loads as well as lines of daily loads variations in raw sewage have been worked out.
Keywords: ścieki; oczyszczalnia ścieków; stężenie zanieczyszczeń; wasterwater; contamination loads; variation of contents of wasterwater